PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TELUR AYAM RAS PADA AGEN TELUR UDIN PASAR INDUK PENYEMBOLUM SENAKEN TANAH GROGOT - Agustomo Agustomo; Amir Hamzah; Ismail Ismail (Paser Institute Management and Busines, 2023)
This research aims to evaluate the influence of product quality and price on the decision to purchase purebred chicken eggs at the Udin Egg Agent at the Pemembolum Senaken Tanah Grogot Main Market. Validity and reliability tests were carried out to ensure the credibility of the research instrument which consists of 19 statements. The results show that all statements are valid and reliable, with a correlation coefficient (R) of 0.896, indicating a strong relationship between product quality (X1), price (X2), and purchasing decisions (Y). Multiple linear regression analysis produces the equation Y = 0.537 + 0.513X1 + 0.359X2, with a coefficient of determination (R2) of 80.3%, indicating that product quality and price contribute 80.3% to purchasing decisions. The results of the F test confirm that simultaneously, product quality and price have a significant effect on purchasing decisions, with Fcount (54.957) > Ftable (3.35). The partial regression coefficient test shows that individually, both product quality (t = 3.644) and price (t = 2.765) have a significant effect on purchasing decisions (Y). The results of the t test state that the most dominant variable influencing purchasing decisions is product quality (X1) with a t count of 3.644 and a significance level of 0.000. These findings contribute to understanding the factors that influence the decision to purchase purebred chicken eggs in the broiler market. The practical implications of this research can help Udin Egg Agents to improve their marketing strategies by focusing on improving the quality of their products.